1998
DOI: 10.1161/01.cir.97.9.900
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Anti–β 2 -Glycoprotein I Antibodies on Endothelial Cells and on the Manifestations of Experimental Antiphospholipid Syndrome

Abstract: Background-The antiphospholipid syndrome (APS) entails a prothrombotic state associated with the presence of anticardiolipin antibodies (aCL). aCL were shown to promote endothelial cell and platelet activation and to induce an APS-like syndrome in mice when administered intravenously. Recent data suggest that aCL target the plasma cofactor ␤ 2 -glycoprotein I (␤2GPI) rather than negatively charged phospholipids. However, it has not been determined whether different epitope-specific anti-␤2GPI antibodies obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
102
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 31 publications
11
102
0
2
Order By: Relevance
“…These findings are in accordance with the pathogenetic activity of both anti-␤ 2 GPI and human mAb 519 in murine passive transfer models of fetal loss in the APS (25,27) and with the reported association between the presence of anti-␤ 2 GPI antibodies and fetal loss (8)(9)(10)(11)(19)(20)(21)(22). In addition, defective placentation might be responsible for some of the early fetal losses reported to frequently occur in women with the APS (51).…”
Section: Simone Et Alsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are in accordance with the pathogenetic activity of both anti-␤ 2 GPI and human mAb 519 in murine passive transfer models of fetal loss in the APS (25,27) and with the reported association between the presence of anti-␤ 2 GPI antibodies and fetal loss (8)(9)(10)(11)(19)(20)(21)(22). In addition, defective placentation might be responsible for some of the early fetal losses reported to frequently occur in women with the APS (51).…”
Section: Simone Et Alsupporting
confidence: 88%
“…Antibodies specific for ␤ 2 GPI have been identified and found to be associated with the clinical manifestations of the antiphospholipid syndrome (APS) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The in vivo immunohistologic demonstration of ␤ 2 GPI on trophoblast surfaces (23,24) and the induction of fetal loss by anti-␤ 2 GPI antibodies in experimental animal models (25,26) suggested a role of anti-␤ 2 GPI antibodies in fetal loss. Moreover, even murine and human aPL monoclonal antibodies (mAb) specifically reacting with anionic PL in the absence of any plasma cofactor have been shown to produce fetal loss, growth retardation, placental deposition, and necrosis in experimental animal models (3,27,28).…”
mentioning
confidence: 99%
“…These findings confirmed and extended the observation that anti-cardiolipin IgG fractions activated EC in the presence of h2GPI [2]. Following these studies, other groups have confirmed this finding by using both polyclonal and monoclonal aPL [5][6][7][8]. Interestingly, aPL-mediated activation with ADM upregulation and pro-inflammatory cytokine secretion was also found with human brain and skin primary EC cultures, suggesting that such an effect might be generalized to EC from different anatomical sites [9].…”
supporting
confidence: 79%
“…b2GP-I is the target auto-antigen in the anti-phospholipid syndrome. In experimental models, it has been demonstrated that immunization with b2GP-I and adoptive transfer of b2GP-I reactive lymphocytes enhances atherogenesis [98,99]. Autoantibodies to b2GP-I can be detected in a substantial proportion of patients with vasculitis.…”
Section: Cd28mentioning
confidence: 99%